The electronic spin state of diradicals obtained from the nuclear perspective: the strange case of Chichibabin radicals - Moise, G; Fernández, S; Joll, K; Vaganov, MV; García, F; Timmel, CR; Peña, D; Ardavan, A (Wiley, 2025)
With a view towards the development of molecular spintronics, non-linear optics, and qubits, a great amount of research effort aims to establish the factors which govern the spin classification of diradicals. Electron spin resonance (ESR) is an indispensable tool for such research. However, in some cases, the mere presence of an ESR spectrum is insufficient to ascertain that the presumed diradical is indeed a triplet state. In a comparative case study of a Chichibabin diradical and a monoradical analogue, we show how the signals from different spin states present in liquid solutions of these species may be disentangled. Ultimately, the correct spin classification depends on ESR techniques which probe the spin quantum number directly. In this work, electron nuclear double resonance experiments reveal that the nuclei provide a clear experimental probe of the electronic spin configuration.